The corrole ring : synthesis, functionalisation and reactions of a biomimetic macrocycle. - Zipp, Caitlin (My University, 2014)
The lability of cobalt(III) in vitamin B12 is thought to come about as a function of its coordination environment. The thermodynamics and kinetics of ligand substitution reactions of vitamin B12a were compared to those of a synthetic, more electron rich, corrole-based biomimetic model. The feasibility of corrole synthesis was established with the synthesis of several corroles with different meso substituents. The biomimetic model was designed such that the central meso position bore a substituent with a terminal imidazole (referred to as the ‘tail’) which might act as an axial ligand for a coordinated cobalt ion while the remaining two meso positions bore water-solubilising glucose substituents. Unfortunately, the biomimetic model was water soluble below pH 4 only. This rendered the model unsuitable for the present study and these water solubilising groups were not incorporated into the final model. The model system used in this work is [10-(2-{[4-(1Himidazol-1-ylmethyl)benzoyl]amino}phenyl)-5,15-diphenylcorrolato]cobalt(III), referred to as DPTC-Co Intermediates of the ‘tail’ meso substituent were found to be polymorphic and five pairs of polymorphs were identified. Polymorphism arose from differences in weak termolecular forces and these differences were evaluated. The stability constants for the binding of various neutral N-, P- and S-donor ligands and anionic N-, S-, I- and C-donor ligands to both vitamin B12a and DPTC-Co were determined in a buffered 80:20 methanol:water solvent system. The more stable binding of neutral ligands to DPTC-Co and anionic ligands to vitamin B12a indicates that the interaction between the metal and an incoming ligand is indeed affected by the metal’s coordination environment. Cobalt(III) in DPTC-Co appeared to favour softer ligands while harder ligands were favoured by vitamin B12a. Kinetic studies showed that the coordination of cyanide to cobalt in vitamin B12a was faster than in DPTC-Co. The reaction between cyanide and vitamin B12a was found to be entropically driven while the reaction with DPTC-Co was enthalpically driven. This suggests that while the reaction between cyanide and vitamin B12a is faster, the reaction between cyanide and DPTC-Co is electronically more labile. The coordination environment of cobalt has been seen to significantly affect its chemistry. Coordination by the more electron rich corrole macrocycle led to a softer and more electronically labile metal then when coordinated by the corrin macrocycle of vitamin B12a.
Keywords: Biomimetics.; Organic compounds - Synthesis.; Macrocyclic compounds.